Digit Ratio (2D:4D) and Relative Age Effect (RAE) in physical fitness testing performance on male and female adolescences - Azam, Zulkhairi; Sanuddin, Nurul Diyana; Isa, Kalam Azad; Mohamed Kassim, Nurul Atikah; Kosni, Norlaila Azura; Muhammad Yazid, Umairah; Ashraf, Ahmad Khusairi (Faculty of Sports Science and Recreation, 2024)
The digit ratio (2D:4D), measure the prenatal testosterone and estrogen exposure, where a lower ratio suggests higher testosterone exposure that has been associated with masculine traits, including aggression and athletic performance. Simultaneously, the relative age effect (RAE) illustrates the advantages in physical performance and sports for individuals born closer to the selection cut-off dates. Despite these associations, research presents mixed findings on the impact of 2D:4D and RAE on physical fitness testing among adolescents, indicating a critical gap in understanding the dynamics between biological and chronological factors in youth fitness performance. Therefore, this study aims to explore the correlation between the role of 2D:4D and RAE with physical fitness performance in male and female adolescents. A cohort of 234 high school students, aged 13 to 17 years old, underwent measurements of height, weight, body mass index, waistto-hip ratio, and 2D:4D participated in six physical fitness tests. Interestingly, the findings reveal no significant correlation between 2D:4D and RAE with physical fitness performance in males, whereas in females, certain associations were observed with 2D:4D correlated with SBJ and RAE are linked with RLHGS (p<0.05). These results underscore the complexity of predicting athletic ability from biological and chronological markers and highlight the necessity for further research to dissect the intricacies influencing fitness outcomes among adolescents.